Starting anew: Entrepreneurial intentions and realizations subsequent to business closure - Veronique Schutjens; Erik Stam (Max Planck Institute of Economics, 2006)
We know that most businesses fail. But what is not known is to what extent failed ex-entrepreneurs set up in business again. The objective of this article is to explore potential and realized serial entrepreneurship. Based on three disciplines - psychology, labour economics, and the sociology of careers - we formulated propositions to explain (potential) serial entrepreneurship. We tested these propositions empirically with a longitudinal database of 79 businesses that had closed within 5 years after start-up. A large majority of the ex-entrepreneurs maintained entrepreneurial intentions subsequent to business closure, while almost one in four business closures were followed by a new business (serial entrepreneurship). Our results show that the determinants of restart intention (potential serial entrepreneurship) and actual restart realization (realized serial entrepreneurship) are different. Ex-entrepreneurs who are young, who worked full-time in their prior business, and who recall their business management experience positively are likely to harbour restart intentions. Only 'being located in an urban region' transpired to have a significant effect on the start of a new business. Although entrepreneurial intentions are a necessary condition for the start of a new business, this study shows that the explanation of entrepreneurial intentions is distinct from the explanation of new business formation subsequent to business closure.
Keywords: 330; serial entrepreneurship; business closure; entrepreneurial intentions; new business formation; The Netherlands